2000
DOI: 10.4049/jimmunol.164.5.2667
|View full text |Cite
|
Sign up to set email alerts
|

Role for IgE in Airway Secretions: IgE Immune Complexes Are More Potent Inducers Than Antigen Alone of Airway Inflammation in a Murine Model

Abstract: IgE is present in airway secretions from human patients with allergic rhinitis and bronchial asthma. However, the contribution of IgE present locally to the overall airway inflammation is not well understood. We hypothesize that Ag-specific IgE can capture airborne Ags and form immune complexes. These immune complexes may function as potent inducers of immune responses in the lung, contributing to the perpetuation of airway inflammation. BALB/c mice were first sensitized with OVA in alum systemically and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 48 publications
(32 reference statements)
3
36
0
Order By: Relevance
“…More interestingly, the sensitization can increase uptake of specific Ag via an endosomal transcellular pathway across tracheal and jejunal epithelium (64,65). Furthermore, in vitro-formed IgE IC, when administered through the airways, are more potent than Ag alone in inducing airway inflammatory responses in mice previously sensitized with the Ag (66). However, these studies did not reveal the CD23-dependent transport of the IC on airway epithelial cells.…”
Section: Discussionmentioning
confidence: 49%
“…More interestingly, the sensitization can increase uptake of specific Ag via an endosomal transcellular pathway across tracheal and jejunal epithelium (64,65). Furthermore, in vitro-formed IgE IC, when administered through the airways, are more potent than Ag alone in inducing airway inflammatory responses in mice previously sensitized with the Ag (66). However, these studies did not reveal the CD23-dependent transport of the IC on airway epithelial cells.…”
Section: Discussionmentioning
confidence: 49%
“…Serum IgE levels correlate with asthmatic symptoms (43). To determine whether the ITK Ϫ/Ϫ mice were generating an IgE response against the allergen, we tested their serum for total IgE and OVAspecific IgE.…”
Section: Increased Total and Ag-specific Ige In Itk Null Micementioning
confidence: 99%
“…Previously we showed that when mice were immunized with Ag systemically and subsequently challenged by the same Ag through the airways, Ag-specific IgE remained detectable in the airways for Ͼ2 wk after the last airway challenge (39). Thus, the airway mast cells should remain sensitized by Ag-specific IgE even after the airway inflammation has subsided and should respond when the animals are provoked with the same Ag through the airways at a later time point.…”
Section: Fc⑀ri␣ ϫ/ϫ Mice Develop Significantly Lower Ahr In Response mentioning
confidence: 99%